Specific immunization of mice against Leishmania mexicana amazonensis using solubilized promastigotes - Barral Netto, Manoel (1987)
Fundação Gonçalo Moniz. Centro de Pesquisas Gonçalo Moniz. Salvador, BA, Brasil / Universidade Federal da Bahia. Salvador, BA, Brasil / Cornell University Medical College. New York, NY